2021
DOI: 10.1186/s12903-021-01778-8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of tweets on toothache during the COVID-19 pandemic using the CrystalFeel algorithm: a cross-sectional study

Abstract: Background Reasons such as the lack of information on the COVID-19 disease, lack of proven treatment for it, uncertainty about the duration of the pandemic, or social isolation affect people’s mental health. This study aimed to analyze the emotional type and intensity in tweets on toothache posted during the COVID-19 pandemic. Methods Using the Twitter Search API, we collected tweets in English associated with the keywords “Corona, Toothache” “Coro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…In this study, 67.8% of the participants stated that they had previously visited the dentist during the pandemic (Q3) and 34.1, 24, and 12% provided pain, caries, and tooth extraction, respectively, as the reasons for the visit (Q3-1). Similarly, as our results, toothache was the first reason for visiting the dentist during the pandemic (Altan et al 2021;Surme et al 2021). It can be concluded that 92.2% of the participants highly counted on the measures taken by their dentists (Q6) and that 72% did not hesitate to take their children to the dentist during the pandemic (Q5).…”
Section: Discussionsupporting
confidence: 87%
“…In this study, 67.8% of the participants stated that they had previously visited the dentist during the pandemic (Q3) and 34.1, 24, and 12% provided pain, caries, and tooth extraction, respectively, as the reasons for the visit (Q3-1). Similarly, as our results, toothache was the first reason for visiting the dentist during the pandemic (Altan et al 2021;Surme et al 2021). It can be concluded that 92.2% of the participants highly counted on the measures taken by their dentists (Q6) and that 72% did not hesitate to take their children to the dentist during the pandemic (Q5).…”
Section: Discussionsupporting
confidence: 87%
“…There was also an increase reported in the use of online searches and social media to address/express oral healthrelated concerns during the pandemic [62,[105][106][107][108][109]. Two studies explored key search terms utilised by those searching online with results showing that "toothache" and "corona-toothache" were used most frequently [105,109].…”
Section: Alternative Models Of Dental Provision and Online Help-seekingmentioning
confidence: 99%
“…There was also an increase reported in the use of online searches and social media to address/express oral healthrelated concerns during the pandemic [62,[105][106][107][108][109]. Two studies explored key search terms utilised by those searching online with results showing that "toothache" and "corona-toothache" were used most frequently [105,109]. One study focused on the use of Twitter throughout the pandemic with people tweeting about oral health impact, types of dental problems, managing symptoms at home, views on consequences of delaying dental treatment and experiences with accessing oral health services [106].…”
Section: Alternative Models Of Dental Provision and Online Help-seekingmentioning
confidence: 99%